Improving Quality Management in Higher Education Institutions in Developing Countries through Strategic Planning - Mensah, Justice (Asian Journal of Contemporary Education, 2020)
The objective of the paper was to provide an overview of strategic planning and how a Strategic Plan (SP) can be developed and implemented effectively in Higher Education Institution (HEIs) in developing countries for continuous quality improvement. Related literature was reviewed and analysed using the narrative synthesis approach. It was established from the review that a SP serves as a framework for determining the quality path a HEI should chart to achieve its desired future. Advantages of strategic planning include; providing opportunity for relevant constituencies to participate in institutional governance, synchronising plans towards achieving institutional goals; prioritising for efficient allocation of resources, and engaging stakeholders for collective ownership of institutional agenda. SPs are developed based on internal and external environmental scan for institutional strengths, weaknesses, opportunities, and threats; and aligned with institutional mission, vision, values, and goals. Issues for consideration in strategic planning may include academic (teaching, research, and extension) matters, institutional governance, finance, infrastructure, Information and Communication Technology, human resource, institutional advancement and internationalisation. Challenges in planning and implementation of SPs in HEIs in developing countries include resource constraints, inadequate expertise and commitment, as well as resistance to change. For effective implementation of a SP, there should be an implementation plan that details who should do what at what time and with which resources. Successful strategic planning and implementation of the Plan depend on commitment of and collaboration among qualified planners, implementers, monitors, evaluators and other relevant stakeholders.